Empowering Women through Mangrove Batik Business in Percut Sei Tuan, North Sumatera - sinaga, Muhammad Zulham efendi; Rambey, Ridahati (Talenta Publisher, 2020)
One of the efforts to improve community welfare is through community empowerment activities. Through the Community Service Program for women's groups in Percut Sei Tuan, it is hoped that women can increase family income. Available natural resources such as natural dyes made from wood around the mangrove forest can be used to support batik products with natural dyes. Types of natural dyes include those from the wood species Rhizopora, Avicennia, Ceriop, Bruguiera. In this service activity the group has made products in the form of handkerchiefs and printed batik cloths.